Nonlinear relationship between incidence of new-onset stroke and plasma atherosclerotic index in middle-aged and older adults - Wang, Qingqing; Zhao, Leiyong; Zuo, Tianqi; Peng, Wei (Frontiers in Neurology, 2025)
BackgroundThe arteriosclerosis index of plasma (AIP) is a sensitive biomarker that reflects characteristics of lipid metabolism and lipoprotein profiles, calculated as the logarithmic transformation of the ratio between fasting triglycerides (TG) and fasting high-density lipoprotein cholesterol (HDL-C). However, current evidence regarding the detailed relationship between AIP and the risk of stroke among middle-aged and elderly adults remains limited. Therefore, this study was conducted to comprehensively explore the link between AIP and the occurrence of new-onset stroke in middle-aged and elderly populations, aiming to provide an evidence-based foundation for stroke prevention and management.MethodsData analyzed in this study were drawn from the China Health and Retirement Longitudinal Study (CHARLS), including 6,808 subjects aged ≥45 years without prior history of stroke. Logistic regression models and restricted cubic spline (RCS) analyses were employed to investigate the association between AIP values and stroke incidence. Subgroup analyses were conducted to examine potential sources of heterogeneity, and stratified analyses were performed to verify the robustness of the results.ResultsFollowing extensive adjustment for potential confounding factors, logistic regression demonstrated that increased AIP was significantly associated with higher stroke incidence among middle-aged and elderly individuals (OR = 1.63, 95% CI: 1.09, 2.45, p = 0.02). RCS analysis further revealed a nonlinear dose–response relationship between AIP and stroke risk, identifying an inflection point at an AIP value of −0.02. Subgroup analyses revealed differences based on sex and age: a linear positive correlation was observed in males but not in females; similarly, no significant correlation appeared in individuals aged 45–59, while a positive correlation emerged in individuals aged 60 and above, with the association strengthening with age. Stratified analysis indicated no statistically significant interactions among strata.ConclusionThis study identifies a nonlinear, positive correlation between AIP and stroke incidence in middle-aged and elderly individuals, noting variations based on gender and age.